“CHALLENGES AND OPPORTUNITIES IN IMPLEMENTING GREEN ACCOUNTING FOR SUSTAINABLE BUSINESSES” (International Journal of Food and Nutritional Sciences, 2023)
Green accounting, also known as environmental accounting, integrates environmental costs into traditional financial accounting practices. This paper explores the challenges and opportunities associated with implementing green accounting in sustainable businesses. It examines the theoretical framework, practical issues, and benefits of adopting green accounting practices. The research employs a qualitative approach, reviewing literature and case studies to provide insights into how businesses overcomes obstacles and leverage opportunities to enhance their sustainability efforts through green accounting.